PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, SISTEM ADMINISTRASI PERPAJAKAN MODERN, TAX AMNESTY DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus pada KPP Pratama Surakarta) - Sulistyowati, Murni; Nuryati, Nuryati (ITB AAS INDONESIA, 2024)
This study aims to provide empirical evidence that variables Knowledge Taxation, Taxpayer Awareness, Modern Tax Administration System, Tax Amnesty And Tax Sanctions have a positive significant effect on Personal Taxpayer Compliance (Case Study on KPP Pratama Surakarta). The population in this study are all individual taxpayers as much 104.192. Sampling in this research use Accidental Sampling 100 respondents. The results of the analysis test show that Tax Knowledge, Taxpayer Awareness, Modern Tax Administration System, Tax Amnesty and Tax Sanction have positive and significant impact on Personal Taxpayer Compliance..The result of R2 test shows the variable of Tax Knowledge Influence, Taxpayer Awareness, Modern Tax Administration System, Tax Amnesty and Tax Sanction able to explain 93,4% to variable of Personal Taxpayer Compliance while others equal to 6,6% explained by other variable outside research model.